Metodología de conformación de lotes de arcilla para la industria cerámica del área metropolitana de Cúcuta a partir de análisis fisicoquímicos y modelado de mezclas (2020)
The metropolitan area of Cúcuta (Colombia) is characterized by the existence of several companies dedicated to the manufacture of ceramic construction materials. The existence of these companies is caused by the high availability of red clays of sedimentary type that abound in this territory. Due to the goodness of the clay in the region, many entrepreneurs do not carry out activities aimed at obtaining a homogeneous raw material to be used in the manufacturing process of tiles, roof tiles and masonry ceramics. Although this fact does not have major disadvantages for the production that is sold in the local and national market, the same does not happen for the sales abroad, due to the variability between production batches caused by lack of homogeneity of the raw material used. From this problematic the authors developed this study with the purpose of finding a methodology that allows to reduce the heterogeneity of the argillaceous raw materials. The work consisted in making a comparative analysis between the methodology of random cutting with cone type homogenization and the mechanized trench methodology. Chemical analysis was carried out by X-ray fluorescence, mineralogical characterization by means of X-ray diffraction and physical-ceramic characterization (sand percentage, firing shrinkage and mechanical resistance to flexion) based on the guidelines of the Colombian technical standard for this kind of materials. It was evidenced that the trench methodology allows greater homogeneity in the results of the technological variables evaluated.